Contribution of Sectoral Credit on the Economic Growth of Nepal (SS Multidisciplinary Research Journal, 2024)
This research paper investigates the contribution of sectoral credit to the economic growth of Nepal. Utilizing a dataset covering quarterly time series data from Fiscal Year 2010/11 quarter 1 to Fiscal Year 2022/23 quarter 2, the study employs an empirical approach to examine the relationship between sectoral credit allocation and gross domestic product (GDP). The analysis focuses on three key sectors: agriculture, service, and industry. The results indicate significant findings in both the long run and short run. In the long run, agricultural sector credit exhibits a negative impact on GDP, while service sector credit shows a positive effect. However, the impact of industrial sector credit is inconclusive. In the short run, agricultural credit positively influences GDP after a certain lag, and service credit has an immediate positive impact.